Enhancing medical student training during psychiatry clerkship through a school-based mental health approach: A qualitative study - Sylas Sebastian Neela Sekhar; Tan Ming Gui; Nicholas Pang Tze Ping; Koh Yunn Min (The Korean Society of Medical Education, 2025)
Purpose: This study evaluated a school-based mental health program within a psychiatry clerkship to enhance medical students’ competencies in mental health literacy, empathy, communication, and adaptability. The program aimed to bridge theoretical knowledge with practical skills through experiential learning in a real-world, community-based setting. Methods: The study utilized convenience sampling to select 32 medical students from the 2023–2024 psychiatry clerkship cohort. Four focus group discussions, each lasting 60–90 minutes, provided qualitative data, which were analyzed using reflexive thematic analysis in Atlas.ti (ATLAS.ti GmbH, Germany) to identify themes related to professional development. Results: Five key themes emerged, highlighting significant gains in context-sensitive communication, empathy, and mental health literacy specific to adolescent issues. The students reported increased clinical confidence, enhanced resilience through psychological techniques such mindfulness and motivational interviewing, and benefited from sustained engagement and peer support, fostering collaboration and stress management. Conclusion: The school-based mental health program enhanced essential competencies in mental health literacy, empathy, communication, and practical skills for medical students. By integrating experiential learning into medical education, the program addressed training gaps, equipping future healthcare providers with the skills necessary for holistic and patient-centered mental healthcare across diverse clinical settings. The approach showed potential for broader applications in medical education to prepare students for comprehensive mental health support skills.